Multi-parameter optimization: Development of a morpholin-3-one derivative with an improved kinetic profile for imaging monoacylglycerol lipase in the brain - He, Yingfang; Grether, Uwe; Taddio, Marco F.; Meier, Carla; Keller, Claudia; Edelmann, Martin R.; Honer, Michael; Huber, Sylwia; Wittwer, Matthias B.; Heer, Dominik; Richter, Hans; Collin, Ludovic; et al. (European journal of medicinal chemistry, 2022)
Monoacylglycerol lipase (MAGL) is a gatekeeper in regulating endocannabinoid signaling and has gained substantial attention as a therapeutic target for neurological disorders. We recently discovered a morpholin-3-one derivative as a novel scaffold for imaging MAGL via positron emission tomography (PET). However, its slow kinetics in vivo hampered the application. In this study, structural optimization was conducted and eleven novel MAGL inhibitors were designed and synthesized. Based on the results from MAGL inhibitory potency, in vitro metabolic stability and surface plasmon resonance assays, we identified compound 7 as a potential MAGL PET tracer candidate. [11C]7 was synthesized via direct 11CO2 fixation method and successfully mapped MAGL distribution patterns on rodent brains in in vitro autoradiography. PET studies in mice using [11C]7 demonstrated its improved kinetic profile compared to the lead structure. Its high specificity in vivo was proved by using MAGL KO mice. Although further studies confirmed that [11C]7 is a P-glycoprotein (P-gp) substrate in mice, its low P-gp efflux ratio on cells transfected with human protein suggests that it should not be an issue for the clinical translation of [11C]7 as a novel reversible MAGL PET tracer in human subjects. Overall, [11C]7 ([11C]RO7284390) showed promising results warranting further clinical evaluation. [Display omitted] •Eleven morpholin-3-one derivatives were designed and synthesized as novel reversible MAGL inhibitors.•Selection of a potential PET tracer candidate via multiple parameters including target affinity, binding kinetics and metabolic stability in vitro.•PET studies of [11C]7 demonstrated an improved kinetic profile and increased brain uptake for neuroimaging.•Invivo target engagement of [11C]7 in the mouse brain was proved by the pretreatment with a selective MAGL inhibitor.